Shocklets, SLAMS, and field‐aligned ion beams in the terrestrial foreshock. Issue 3 (6th March 2013) - Wilson, L. B.; Koval, A.; Sibeck, D. G.; Szabo, A.; Cattell, C. A.; Kasper, J. C.; Maruca, B. A.; Pulupa, M.; Salem, C. S.; Wilber, M.
<x xml:space="preserve">Abstract</x> [1] We present Wind spacecraft observations of ion distributions showing field‐aligned beams (FABs) and large‐amplitude magnetic fluctuations composed of a series of shocklets and short large‐amplitude magnetic structures (SLAMS). The FABs are found to have Tb 80 − 850 eV, Vb/Vsw 1. 3 − 2. 4, T⊥, b/T∥, b 1–8, and nb/no 0.2–11%. Saturation amplitudes for ion/ion resonant and non‐resonant instabilities are too small to explain the observed SLAMS amplitudes. We show two examples where groups of SLAMS can act like a local quasi‐perpendicular shock reflecting ions to produce the FABs, a scenario distinct from the more common production at the quasi‐perpendicular bow shock. The SLAMS exhibit a foot‐like magnetic enhancement with a leading magnetosonic whistler train, consistent with previous observations. Strong ion and electron heating are observed within the series of shocklets and SLAMS with temperatures increasing by factors ≳ 5 and ≳ 3, respectively. Both the core and halo electron components show strong perpendicular heating inside the feature.